Weathering crust formation outpaces melt-albedo feedback on blue ice shelves of East Antarctica - Giacomo Traversa; Biagio Di Mauro (Communications Earth & Environment)
Abstract The penetration of shortwave radiation beneath glacier surfaces has the potential to induce melting leading to the formation of a porous white layer commonly known as weathering crust. Very little is known about its role in the Antarctic Ice Sheet. Here we provide unprecedented observational evidence for the weathering crust formation over blue ice areas of ice shelves of the Northern Victoria Land in austral summer 2022–2023, by means of in-situ and remote-sensing observations. Then, we estimated the radiative impact of the weathering crust, demonstrating a predominant negative albedo feedback over blue ice areas (on 93% of the study area), with respect to positive melt-albedo feedback (supraglacial-pond formation). Furthermore, weathering crust occurred after a period of increasing temperature, relative humidity, low wind speed and clear sky conditions. Moreover, we claim that this new process should be included in regional climate modelling of the Antarctic Ice Sheet.